Pengetahuan Orangtua dan Penerapan Protokol Kesehatan Pencegahan Covid-19 Pada Anak Prasekolah - Endar Timiyatun; Taufiq Kariyadi; Eka Oktavianto (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2023)
Background of Study: The Covid-19 pandemic has been declared as a global pandemic by the World Health Organization (WHO) since March 2020 and in Indonesia it has been declared as a type of disease that causes a public health emergency. Covid-19 can be transmitted from person to person through coughing droplets or saliva. Parental knowledge and good application of the Covid-19 health protokol in pre-school children are very important so that there is no cause an increase in the number of Covid-19 cases and prevent the spread of Covid-19 infection cases in pre-school children. Objective this study is to determine the relationship between parental knowledge and the implementation of the Covid-19 health protokol in pre-school children.Methods: non-experimental type with a cross sectional research design was used in this research. The population of this study were parents of preschool children at PAUD Little Care Surya Global Yogyakarta. The total population was 40 people. Total sampling was used as sampling technique. The instruments used were in the form of a Covid-19 prevention knowledge questionnaire and a questionnaire on the implementation of the Covid-19 prevention protokol which was developed by the researcher himself. The statistical test used was the Kendall's Tau test.  Results: The majority of parents' knowledge of the Covid-19 health protokol was in the good category, as many as 30 respondents (75.0%). The implementation of the covid 19 health protokol for preschool children was mostly in the good category, as many as 32 respondents (80.0%). Parents who have good knowledge of Covid-19 prevention health protocols will tend to apply good health protocols to their children. The results of the Kendall tau statistical test obtained a correlation coefficient value of 0.422 with p value = 0.007 (p-value 0.05).Conclusion: There was a relationship between parental knowledge and the application of health protocols in preschool children at Little Care Surya Global Yogyakarta.Keywords: Parents; knowledge; preschool children; Covid-19.